Getreidehandel und Exportbeschränkungen während des Ukrainekrieges - Linde Johanna Götz; Miranda Svanidze (Wirtschaftsdienst, 2023)
Der Ukrainekrieg hat zu einem Rückgang der Weizenausfuhren aus Russland und der Ukraine nach Afrika geführt, die jedoch durch gesteigerte Exporte anderer Länder nahezu ausgeglichen wurden. Weltweite Beschränkungen der Weizenexporte sowie die Unsicherheit, dass Russland seine Getreideexporte als Waffe nutzt und die Schwarzmeer-Getreide-Initiative ausgesetzt wird, haben die Getreidepreise zusätzlich drastisch ansteigen lassen. – – Supply chain disruptions related to the Ukraine war have led to a decline in wheat exports from Russia and Ukraine to African countries, which has been largely offset by an increase in wheat exports from other countries. However, fears that disruptions in the grain supply chain will be exacerbated by Russia's use of grain exports as a weapon and the expansion of economic and financial sanctions by Western countries, as well as the threat of the termination of the Black Sea Grain Initiative, have greatly increased risks in the global grain supply chain. Food security in African countries has therefore been mainly negatively affected by rising food prices, which have limited access to food and thus food security.
Keywords: Q17; Q13; Q18; F13; 330; Weizen; Getreidepreis; Export; Kriegsfolgen; Russland; Ukraine; Welt